Originally Posted by

**Antalya** I need somebody to complete this little task, I wouldn't ask if there was a chance for me to understand this, but I don't until somebody complete this task.

Task:

a) Use logarithm rules to simplify the expression.

$\displaystyle lg a^{3}-lg(a^{2}b^{4})+2lg\frac{b^{2}}{a}$

b) Find the equations of the two asymptotes of the function g, where

$\displaystyle g(x)=\frac{2x+1}{x-1}$

Correct answer:

a) $\displaystyle -lga(=lg\frac{1}{a})$

b) Vertical asymptote: x = 1

Horizontal asymptote: y = -2

I need full calculation in order.